Instagram Live Interactive Features as a Cutting-Edge Health Communication Tool Examining Literature Review - Rahayu, Agustin Putri; Feriyanti, Alma (Panakeia Journal of Epidemiology, 2024)
The digital transformation of health communication has experienced a period of accelerated growth, with social media platforms such as Instagram Live emerging as a particularly innovative feature in the field of health promotion. The objective of the research was to examine health communication strategies based on Instagram Live. The PRISMA literature review methodology, conducted from 2020 to 2024, revealed comprehensive strategies for effective health communication on Instagram Live. These strategies included an optimal duration of 20 to 60 minutes, the selection of attractive and competent moderators and health professionals, the presentation of health topics in alignment with trending issues, the use of clear and research-based content, visually appealing presentations, the archiving of Instagram Live sessions as reels, and the creation of emotional communication spaces through storytelling approaches and strategic hashtag usage. These strategies significantly enhanced health literacy and reduced information disparities in society.